IMPLEMENTASI KEBIJAKAN PEMBANGUNAN INFRASTRUKTUR DI DESA BUHO-BOHO KECAMATAN MOROTAI TIMUR KABUPATEN PULAU MOROTAI - LABAKA, TRIO YATNO; RARES, JOYCE; KIYAI, BURHANUDDIN (Sam Ratulangi University, 2021)
Infrastructure development is one of the key and vital aspects to accelerate the national development process, infrastructure also plays an important role as one of the driving wheels of economic growth. In the implementation of village infrastructure, adequate human resources are needed so that the development process can run effectively and efficiently. In this study the author uses the theory of Charles O Jones which suggests about policy implementation,namely implementation is the set of activities directed toward putting a program into effect. Which consists of three main activities that are very important, namely Organization,Implementation, and application this research user deseriptive qualitive research method. The results generally explain that the implementation of infrastructure,development policies in Buho-Buho village, east Morotai District, Morotai Island Regeney has not run optimally because the Buho-Buho village govermment does not yet have adequate human resourcesKeywords: Policy implementation, Development, Infrastructure.